Variasi Bahasa Anak Usia Dini Di Desa Pajukukang Kabupaten Bantaeng - Wahidah Z, St; Rahman, Juliana (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to describe the language variations used by early childhood (young children) in Pajukukang Village, Bantaeng Regency. The main focus of this research is on the forms of language variation that emerge in children's daily interactions, whether in the context of play, communication with peers, or with adults. A qualitative approach with a descriptive method was employed to portray the natural linguistic phenomena in the children’s social environment. Data were collected through direct observation, interviews with parents and teachers, as well as recordings of children’s conversations. The findings reveal that language variation among children in this area is influenced by several factors, including ethnic background, family environment, and social interactions. The children tend to use a mixture of the regional language (Makassar) and Indonesian, forming a unique variation that reflects both language development and their local identity. These findings are expected to contribute to the field of child sociolinguistics and serve as a consideration in the development of early childhood language education in multilingual areas.